Ecospirituality: The psychology of moral concern for nature. (May 2023) - Billet, Matthew I.; Baimel, Adam; Sahakari, Sakshi S.; Schaller, Mark; Norenzayan, Ara
Abstract: People across time and cultures have often conceived of nature, and humanity's connection to it, as essentially spiritual. Yet the psychological literature about this "ecospiritual" orientation has been meager. In eight samples, recruited from the USA, Canada, UK, and Singapore (Total N  = 8795), we investigated the relationship between ecospirituality and moral concern for nature. We developed and validated an 8-item measure of ecospirituality for this purpose. Ecospirituality, over and above environmental attitudes, environmentalist identity, and political orientation, uniquely predicted several aspects of moral concern for nature, such as including nature in one's moral circle, treating nature as a sacred value, and endorsing a reasoning style that places importance on principles and duties to nature. This reasoning style was reflected in decisions involving nature-economic trade-offs, as well as in an unconditional voting style for the Green Party. We discuss how a spiritual view of nature is an important component of the moral psychology of the human-nature relationship, and what implications it might have for interventions aimed at increasing sustainability. Highlights: Spiritual views about nature (ecospirituality) were assessed in online surveys administered in multiple countries. Ecospiritual beliefs were common, even across religious and political divides. Ecospirituality independently predicted multiple measures of moral concern for nature. Ecospiritual participants used principle-based reasoning (rather than cost-benefit) when making decisions about nature. This had implications for decisions involving industrial development and political voting.